Inactivation of FOXA2 by Respiratory Bacterial Pathogens and Dysregulation of Pulmonary Mucus Homeostasis - Choi, Woosuk; Choe, Shawn; Lau, Gee W. (Frontiers in Immunology, 2020)
Forkhead box (FOX) proteins are transcriptional factors that regulate various cellular processes. This minireview provides an overview of FOXA2 functions, with a special emphasis on the regulation airway mucus homeostasis in both healthy and diseased lungs. FOXA2 plays crucial roles during lung morphogenesis, surfactant protein production, goblet cell differentiation and mucin expression. In healthy airways, FOXA2 exerts a tight control over goblet cell development and mucin biosynthesis. However, in diseased airways, microbial infections and proinflammatory responses deplete FOXA2 expression, resulting in uncontrolled goblet cell hyperplasia and metaplasia, mucus hypersecretion, and impaired mucociliary clearance of pathogens. Furthermore, accumulated mucus clogs the airways and creates a niche environment for persistent microbial colonization and infection, leading to acute exacerbation and deterioration of pulmonary function in patients with chronic lung diseases. Various studies have shown that FOXA2 inhibition is mediated through induction of antagonistic EGFR and IL-13R-STAT6 signaling pathways as well as through posttranslational modifications induced by microbial infections. An improved understanding of how bacterial pathogens inactivate FOXA2 may pave the way for developing therapeutics that preserve the protein’s function, which in turn, will improve the mucus status and mucociliary clearance of pathogens, reduce microbial-mediated acute exacerbation and restore lung function in patients with chronic lung diseases.